AJARAN SOSIAL DAN IMPLIKASINYA TERHADAP PERILAKU PENGIKUTNYA (STUDI KASUS TAREKAT NAQSYABANDIYAH KHOLODIYAH DI SOKARAJA BANYUMAS) - Khusnul Khoimah (Jurnal Penelitian Agama, 2015)
Abstract: The results of this study show that tarekat (congregations) should aim to increase the degree of Ihsan with various rituals that accompany it, in order to improve the moral and spiritual perfection. But in the era of globalization, many people think is not responsive to the advancement of age (anti-progress). In fact, the congregation became a place for salik to avoid the bustle of the world lives. Tarekat should hold social change and must be explained in three aspects, religious, social and even political. However, such an assumption does not occur in the Naqshbandi Kholidiyah Sokaraja Banyumas. This congregation is to have a social doctrine that affect the social behavior of his followers, both in the fields of religion, social, economic and political as explored in this study. Keywords: Doctrine, Naqshbandi Kholidiyah Sokaraja, Social Behavior